Explorative Analysis of Securities Crowdfunding: Pillars, Business Flow and Risk Mitigation in MSME Funding in Indonesia - Wahyu Winoto; Permata Wulandari (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This research aims to dig deeper into the SCF industry by identifying essential pillars in the SCF ecosystem and their role in MSME funding, elaborating business processes in the SCF industry in Indonesia, and further exploring the risk mitigation carried out by SCF organizers for investors. The methodology used is a Qualitative Multicase Approach, which can be expressed in 2 proportions, namely proportion one, where there are far more supporting pillars in the SCF ecosystem in Indonesia compared to other countries because SCF in Indonesia is part of the capital market industry where Indonesia this industry is highly regulated and supervised. (highly regulated) and proportion 2, practice in Indonesia, the business flow of SCF funding will be more complex compared to other countries because many parties are involved in protecting the risks on investment that investors may experience. This study has practical implications, where we can see the ecosystem in the SCF industry and how it is practiced in Indonesia compared to other countries so that we, as Indonesians, can participate and contribute to advancing the SCF industry in Indonesia. This research brings novelty because it explains the essential pillars and business processes of the SCF industry, which are more complex in Indonesia than in other countries